Pathologic anatomy of the soft palate, part 2: The soft tissue lever arm, pathology, and surgical correction - Michael H Carstens (Wolters Kluwer Medknow Publications, 2017)
Pathologic anatomy of the soft palate, part 2: The soft tissue lever arm, pathology, and reconstruction. In part two, we consider the soft tissue components of the soft palate: Epithelium, fascia, muscles, arterial supply, and innervation. These velar tissues constitute a functional "lever arm" for control of speech and swallowing. Fascia and peripheral nerves arise neural crest originating from rhombomeres 2-7. Muscles arise from paraxial mesoderm (PAM) of somitomeres 4, 6, and 7. Lateral plate mesoderm lying outside of PAM provides the building blocks of the circulatory system. Neurovascular analysis discloses the soft palate to have three developmental zones with distinct sources of neurovascular supply. Emphasis is placed on the anterior third of the palatine aponeurosis; this critical structure determines where the levator complex will insert. The basic field defect of soft palate clefts arises from insufficiency of the lesser palatine neurovascular pedicle affecting the posterior palatine shelf and anterior 1/3 of the palatine aponeurosis. This leads to forward displacement of the levator complex and pathologic insertion onto the bony margin of the cleft site. Soft-tissue disruption will then be presented in terms of the simple genetic loop between bone morphogenetic protein 4 (BMP-4) and Sonic hedgehog. The migration of soluble factors such as BMP-4 from their origin with developing bone to the free border of the epithelium permitting fusion of adjacent structures.